Нова версія аналогового симулятора SPICE - Ришко, С. А. (ХНУРЕ, 2024)
SPICE (Simulation Program with an Emphasis on Integrated Circuits) has long been the primary tool for engineers used to simulate analog circuits. However, with the increasing availability of simulation tools, many of which are open source or free to use, questions have arisen such as their ability to support the latest broadband devices. One notable limitation is that existing SPICE programs may not have the device equations required to correctly model SiC and GaN devices.
Keywords: аналоговий симулятор SPICE; пристрої на основі SiC